2015
DOI: 10.1373/clinchem.2015.242081
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Ultrasensitive Digital Immunoassay for Cardiac Troponin I Based on Single Molecule Array Technology

Abstract: BACKGROUND:The association between increases in cardiac troponin and adverse cardiac outcomes is well established. There is a growing interest in exploring routine cardiac troponin monitoring as a potential early indicator of adverse heart health trends. Prognostic use of cardiac troponin measurements requires an assay with very high sensitivity and outstanding analytical performance. We report development and preliminary validation of an investigational assay meeting these requirements and demonstrate its app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…47 Disadvantages of the method are that it requires relatively large sample volumes, up to 100 uL, and is limited to single proteins. 23 Another method referred to as digital ELISA, offered by Quanterix (Lexington, MA), has also been shown to detect troponin in this lower range 48 and is based on analyte enrichment with microbeads which are each loaded into a femtoliter microwell, avoiding antibody cross-reactions, and converted to fluorescence products using enzymatic methods. 49 Digital ELISA has been multiplexed to measure six low-abundance cytokines in parallel.…”
Section: Increasing the Sensitivity Of Immunoaffinity Assays To Singlmentioning
confidence: 99%
“…47 Disadvantages of the method are that it requires relatively large sample volumes, up to 100 uL, and is limited to single proteins. 23 Another method referred to as digital ELISA, offered by Quanterix (Lexington, MA), has also been shown to detect troponin in this lower range 48 and is based on analyte enrichment with microbeads which are each loaded into a femtoliter microwell, avoiding antibody cross-reactions, and converted to fluorescence products using enzymatic methods. 49 Digital ELISA has been multiplexed to measure six low-abundance cytokines in parallel.…”
Section: Increasing the Sensitivity Of Immunoaffinity Assays To Singlmentioning
confidence: 99%
“…In a research the level of cTnI was significantly higher in heart failure patients, and exhibited increasing precise concentrations with rising New York Heart Association classification of heart failure severity, which meant cTnI is an accurate indicator for the diagnosis of heart failure [32]. There are also other studies demonstrated that the release of cTnI is associated with increased 1 year mortality and heart failure related readmission, and the cTnI level can act as an independent predicator, and complete in prognostic utility of CHF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…The sandwich-type immunosensor format allocates 40 min to allow for cTnI binding and an additional 80 min to accommodate the binding of the IRMOF-based detection probe. An alternative high sensitivity fluorescence-based detection assay capitalises on Single-molecule Array (Simoa) technology [123]. Simoa is based on “the simultaneous counting of singulated capture microbeads” to detect the target analyte [124].…”
Section: Evaluating Ctni Detection Techniquesmentioning
confidence: 99%
“…Figure 3 and Figure 4: [37,38,48,49,50,57,58,61,65,66,68,69,70,71,74,84,85,86,87,88,89,93,94,95,96,97,104,105,111,112,115,116,117,120,121,122,123,125,126,127,128,130,132,133,134,136,138,144,145,148,150,151,159,161,174,175,176,184,185,186,187,188,189,190,…”
Section: Reprinting Figuresmentioning
confidence: 99%